Employee Productivity Model at Mineral, Coal and Geothermal Resources Center - A Riyanto; M L Nurfachsya; G Sianturi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study intends to determine the influence of Organizational Culture and Work Environment on Work Productivity, either partially or simultaneously, this research was carried out at the Center for Mineral, Coal and Geothermal Resources. The population in this study amounted to 161 employees at the Center for Mineral, Coal and Geothermal Resources. Sampling was used in taking samples in this study using a census with a total sample of 62 respondents. Based on the variables studied, the types of research used are descriptive and verification. The analytical method used in this research is multiple linear regression, correlation coefficient, determination analysis coefficient, partial and simultaneous hypothesis testing. This study obtained the results that organizational culture has a significant influence on work productivity, and the work environment does not have a significant effect on work productivity. The results of the research show that both orientations can be applied simultaneously in determining work productivity in the Center for Mineral, Coal and Geothermal Resources. The results of this study are expected to help managers in the company to increase the work productivity of their employees by paying attention to Organizational Culture and Work Environment on Work Productivity.